2015
DOI: 10.1038/mp.2015.29
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine network analysis of cerebrospinal fluid in myalgic encephalomyelitis/chronic fatigue syndrome

Abstract: Myalgic encephalomyelitis/chronic fatigue syndrome is an unexplained debilitating disorder that is frequently associated with cognitive and motor dysfunction. We analyzed cerebrospinal fluid from 32 cases, 40 subjects with multiple sclerosis and 19 normal subjects frequency-matched for age and sex using a 51-plex cytokine assay. Group-specific differences were found for the majority of analytes with an increase in cases of CCL11 (eotaxin), a chemokine involved in eosinophil recruitment. Network analysis reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 49 publications
3
77
0
Order By: Relevance
“…We sampled only peripheral blood and not other compartments such as cerebrospinal fluid (CSF). Cytokine studies in the CSF of ME/CFS patients have reported abnormalities even though the sample size has been modest and simultaneous serum samples were not analyzed (54,55). In one study, a diathesis to allergic and inflammatory responses in CSF, similar to some of our findings, were found in these patients (54,55).…”
Section: Discussionsupporting
confidence: 66%
“…We sampled only peripheral blood and not other compartments such as cerebrospinal fluid (CSF). Cytokine studies in the CSF of ME/CFS patients have reported abnormalities even though the sample size has been modest and simultaneous serum samples were not analyzed (54,55). In one study, a diathesis to allergic and inflammatory responses in CSF, similar to some of our findings, were found in these patients (54,55).…”
Section: Discussionsupporting
confidence: 66%
“…A decrease in IL-10 favors an increase in pro-inflammatory responses, and this may increase the prevalence of Th1-like cytokines. Importantly, we and others have reported significant reductions in IL-10 from CFS/ME patients 58,59…”
Section: Discussionsupporting
confidence: 50%
“…We used NodeXL to build within group analyte network diagrams (Hornig et al , 2015; Smith et al , 2010). Network analysis was utilized to understand the relationships between analytes and identify connection patterns.…”
Section: Methodsmentioning
confidence: 99%